Issue Information. Issue 8 (29th August 2022) - Unknown
Abstract : Cover : The world of small RNA research was revolutionized by high‐throughput sequencing, which facilitated the identification of novel RNA species without any prior knowledge of their sequence. The diverse biogenesis pathways that give rise to different small RNA classes, however, produces many small RNAs that harbor internal modifications and chemical signatures at their terminal RNA nucleotides, which can interfere with standard cloning protocols and, thus, detection and identification. In this issue, Crocker et al provide guidance on how to design small RNA cloning workflows in eukaryotes that most accurately capture specific small RNAs of interest, by addressing their specific molecular features for successful cloning and sequencing. The cover image depicts the landscape of small RNAs in eukaryotes and the additional transcripts that can be detected when small RNA molecular features are resolved for recovery of these RNAs during cloning. Image provided by the authors.